2016
DOI: 10.1093/eurpub/ckw068
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of migrants and ethnic minorities in European birth cohort studies—a scoping review

Abstract: The majority of European birth cohorts assessed participants' migration history or ethnic background; however, this information was seldom used for comparative analyses in trying to disentangle reasons for health inequalities. Also, heterogeneous indicators were used. Better use of data already available, as well as harmonization of data collection on migration history and ethnicity, could yield interesting insights into the production of health inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Second, we collected detailed information on migration status: in Germany, there are few studies looking at health and healthcare differences between groups with different migration statuses since hospital data, registries or administrative data do not capture migration background. In addition, our recruitment strategy sought to include a high proportion of women with migration background, in an effort to avoid the common lack of inclusion of minority populations in cohort studies [29].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Second, we collected detailed information on migration status: in Germany, there are few studies looking at health and healthcare differences between groups with different migration statuses since hospital data, registries or administrative data do not capture migration background. In addition, our recruitment strategy sought to include a high proportion of women with migration background, in an effort to avoid the common lack of inclusion of minority populations in cohort studies [29].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, the risk of thyroid cancer among the women exposed to reproductive medication was found to be much greater in Danish women compared with US women. To our knowledge, studies concerning Western women to date have included few Asian women . It is not clear how to generalize findings in Western women to infertile Asian women.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, studies concerning Western women to date have included few Asian women. [4][5][6] It is not clear how to generalize findings in Western women to infertile Asian women. To our knowledge, no large study has been conducted to date among Asian women to evaluate the relationship between risk of thyroid cancer and use of reproductive medications.…”
Section: Introductionmentioning
confidence: 99%
“…Although the USA has the highest total number of immigrants in the world, and the highest funding on medical research, this pattern is probably a consequence of research politics in the country encouraging trials to report information on the ethnicity of participants, 23 which can be used in immigration studies. However, a recent scoping review of birth cohort studies in 20 European countries reported that, although 70% of them collected information about migration history or ethnicity, only 26% used that information for data analyses or planned to do so 24 . Countries in the Middle East, with the highest levels of immigration in the world, were poorly represented in our material, as were countries with less inclusive or responsive health systems and restrictive integration policies, such as most of Central and Southeast Europe 25 …”
Section: Discussionmentioning
confidence: 99%